COUNSELING ON A HEALTHY LIFESTYLE WITHOUT STOMACH ACID (GERD) AND URIC ACID IN BAH JOGA VILLAGE, SIMALUNGUN REGENCY - Halijah, Siti; Suraya, Rani; Asnawi, Azi; Audiansyah, Wanda; Hairul, Hairul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Aging is a natural stage in human life accompanied by physical and health changes. In Bahjoga Village, Indonesia, people face specific health challenges as they age, including digestive disorders (GERD) and gout. This extension aims to provide practical guidance on healthy living and integrate scientific knowledge with local values. The focus includes a healthy diet, regular physical activity, stress management, and the use of traditional herbs. Through counseling, the community is expected to adopt practical steps to live a healthy life without digestive disorders and gout. The research method involved counseling, outreach, and measuring knowledge before and after the counseling, and the health seminar participants totaled 29 people. The results showed a significant increase in people's understanding of GERD and gout after counseling. The implication is that counseling plays an important role in providing information and encouraging healthy lifestyles. This research underscores the important role of counseling in raising awareness and preventive action on certain health problems, as well as providing a strong basis for continuing extension efforts.